Amplification and over‐expression of MAP3K3 gene in human breast cancer promotes formation and survival of breast cancer cells. Issue 1 (January 2014) - Fan, Yihui; Ge, Ningling; Wang, Xiaosong; Sun, Wenjing; Mao, Renfang; Bu, Wen; Creighton, Chad J; Zheng, Pingju; Vasudevan, Sanjeev; An, Lei; Yang, Jinshu; Zhao, Yi‐Jue; et al.
Abstract Gene amplifications in the 17q chromosomal region are observed frequently in breast cancers. An integrative bioinformatics analysis of this region nominated the MAP3K3 gene as a potential therapeutic target in breast cancer. This gene encodes mitogen‐activated protein kinase kinase kinase 3 (MAP3K3/MEKK3), which has not yet been reported to be associated with cancer‐causing genetic aberrations. We found that MAP3K3 was amplified in approximately 8–20% of breast cancers. Knockdown of MAP3K3 expression significantly inhibited cell proliferation and colony formation in MAP3K3‐amplified breast cancer cell lines MCF‐7 and MDA‐MB‐361 but not in MAP3K3 non‐amplified breast cancer cells. Knockdown of MAP3K3 expression in MAP3K3‐amplified breast cancer cells sensitized breast cancer cells to apoptotic induction by TNFα and TRAIL, as well as doxorubicin, VP‐16 and fluorouracil, three commonly used chemotherapeutic drugs for treating breast cancer. In addition, ectopic expression of MAP3K3, in collaboration with Ras, induced colony formation in both primary mouse embryonic fibroblasts and immortalized human breast epithelial cells (MCF‐10A). Combined, these results suggest that MAP3K3 contributes to breast carcinogenesis and may endow resistance of breast cancer cells to cytotoxic chemotherapy. Therefore, MAP3K3 may be a valuable therapeutic target in patients with MAP3K3‐amplified breast cancers, and blocking MAP3K3 kinase activity with a small molecule inhibitor may sensitize MAP3K3‐amplified breast cancer cells to chemotherapy. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.